Kinsenoside attenuates osteoarthritis by repolarizing macrophages through inactivating NF-κB/MAPK signaling and protecting chondrocytes - Feng Zhou; Jingtian Mei; Xiuguo Han; Hanjun Li; Shengbing Yang; Minqi Wang; Linyang Chu; Han Qiao; Tingting Tang (Elsevier, 2019)
The objective was to investigate the effect of kinsenoside (Kin) treatments on macrophage polarity and evaluate the resulting protection of chondrocytes to attenuate osteoarthritis (OA) progression. RAW264.7 macrophages were polarized to M1/M2 subtypes then administered with different concentrations of Kin. The polarization transitions were evaluated with quantitative real-time polymerase chain reaction (qRT-PCR), confocal observation and flow cytometry analysis. The mechanism of Kin repolarizing M1 macrophages was evaluated by Western blot. Further, macrophage conditioned medium (CM) and IL-1β were administered to chondrocytes. Micro-CT scanning and histological observations were conducted in vivo on anterior cruciate ligament transection (ACLT) mice with or without Kin treatment. We found that Kin repolarized M1 macrophages to the M2 phenotype. Mechanistically, Kin inhibited the phosphorylation of IκBα, which further reduced the downstream phosphorylation of P65 in nuclear factor-κB (NF-κB) signaling. Moreover, Kin inhibited mitogen-activated protein kinases (MAPK) signaling molecules p-JNK, p-ERK and p-P38. Additionally, Kin attenuated macrophage CM and IL-1β-induced chondrocyte damage. In vivo, Kin reduced the infiltration of M1 macrophages, promoted M2 macrophages in the synovium, inhibited subchondral bone destruction and reduced articular cartilage damage induced by ACLT. All the results indicated that Kin is an effective therapeutic candidate for OA treatment. KEY WORDS: Kinsenoside, Osteoarthritis, Macrophages, Polarization, Chondrocytes